COVID-19 and the global political economy : crises in the 21st century - Di Muzio, Tim; Dow, Matt (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Covid-19 and the Global Political Economy investigates and explores how far and in what ways the Covid-19 pandemic is challenging, restructuring, and perhaps remaking aspects of the global political economy. Since the 1970s, neoliberal capitalism has been the guiding principle of global development: fiscal discipline, privatisations, deregulation, the liberalisation of trade and investment regimes, and lower corporate and wealth taxation. But, after Covid-19, will these trends continue, particularly when states are continuing to struggle with overcoming the pandemic and violating one of neoliberalism's key principles: balanced budgets? The pandemic has exposed the fragility of the global political economy, and it can be argued that the intensification of global trade, tourism, and finance over the past 30 years has facilitated the spread of infectious diseases such as Covid-19. Economies in lockdown, jittery markets, and massive government spending have therefore caused a re-evaluation. This volume brings together leading and upcoming critical scholars in international relations and international political economy to provide novel, timely, and innovative research on how the Covid-19 pandemic is impacting (and will continue to impact) the global economy in important dimensions including state fiscal policy, monetary policy, the accumulation of debt, health and social reproduction, and the future of austerity and the fate of neoliberalism. This book will be of great interest to students, scholars, and experts in the fields of international relations and international political economy, as well as history, anthropology, political science, sociology, cultural studies, economics, development studies, and human geography"--
Introduction : The Covid-19 pandemic, international political economy and social reproduction / Matt Dow and Tim Di Muzio -- Global power, inequality, and climate change. "A once in a lifetime opportunity": Covid-19 in the age of finance / Richard H. Robbins -- The billionaire boom : capital as power and the distribution of wealth / Natasha Popcevski -- Neoliberalism, race, and ignorance in an era of Covid-19 / Dan Bousfield -- Covid-19 : decarbonization under duress / Adam Lucas -- Engineering the coronaverse : the wild, wild sovereignty of big meat in the age of the corporate state / Sandy Smith-Nonini -- Global health, social care and reproduction during the Covid-19 Pandemic. Global health, Covid-19, and the future of neoliberalism / Dillon Wamsley and Solomon Benatar -- From Operation Warp Speed to TRIPS : vaccines as assets / Tatiana Andersen -- Covid-19 and the economy of care : disability and aged care services into the future / Laura Davy and Helen Dickinson -- The future of production, money, energy and food regimes. Covid-19 and the future of work : continuity and change in workplace precarity / Tom Barnes, Dani Cotton, and Rakesh Kumar -- MMT, the pandemic and the fiscal deficit fright / Tim Di Muzio -- Carbon capitalism, the social forces of annihilation, and the future of energy / Matt Dow -- Covid-19 and the future of food / Philip McMichael - Conclusion : The ongoing Covid-19 dystopia : a crossroads for critical IPE and humanity / Tim Di Muzio and Matt Dow.
Keywords: International economic relations; International trade; International finance; COVID-19 Pandemic, 2020- -- Economic aspects; POLITICAL SCIENCE / General